Sphingosine kinase 2-deficiency mediated changes in spinal pain processing - Canlas, Jastrow; Holt, Phillip; Carroll, Alexander; Rix, Shane; Ryan, Paul; Davies, Lorena; Matusica, Dusan; Pitson, Stuart M.; Jessup, Claire F.; Gibbins, Ian L.; Haberberger, Rainer V. (Frontiers in Molecular Neuroscience, 2015)
Chronic pain is one of the most burdensome health issues facing the planet (as costly as diabetes and cancer combined), and in desperate need for new diagnostic targets leading to better therapies. The bioactive lipid sphingosine 1-phosphate (S1P) and its receptors have recently been shown to modulate nociceptive signalling at the level of peripheral nociceptors and central neurons. However, the exact role of S1P generating enzymes, in particular sphingosine kinase 2 (Sphk2), in nociception remains unknown. We found that both sphingosine kinases, Sphk1 and Sphk2, were expressed in spinal cord with higher levels of Sphk2 mRNA compared to Sphk1. All three Sphk2 mRNA-isoforms were present with the Sphk2.1 mRNA showing the highest relative expression. Mice deficient in Sphk2 (Sphk2-/-) showed in contrast to mice deficient in Sphk1 (Sphk1-/-) substantially lower spinal S1P levels compared to wild-type C57BL/6 mice. In the formalin model of acute peripheral inflammatory pain, Sphk2-/- mice showed facilitation of nociceptive transmission during the late response, whereas responses to early acute pain, and the number of c-Fos immunoreactive dorsal horn neurons were not different between Sphk2-/- and wild-type mice. Chronic peripheral inflammation (CPI) caused a bilateral increase in mechanical sensitivity in Sphk2-/- mice. Additionally, CPI increased the relative mRNA expression of P2X4 receptor, brain-derived neurotrophic factor and inducible nitric oxide synthase in the ipsilateral spinal cord of wild-type but not Sphk2-/- mice. Similarly, Sphk2-/- mice showed in contrast to wild-type no CPI-dependent increase in areas of the dorsal horn immunoreactive for the microglia marker Iba-1 and the astrocyte marker GFAP. Our results suggest that the tightly regulated cell signalling enzyme Sphk2 may be a key component for facilitation of nociceptive circuits in the CNS leading to central sensitization and pain memory formation.